HUBUNGAN BEBAN KERJA DENGAN KINERJA TENAGA KEPERAWATAN - Ridwan, Junaina; Hartono, Budi; Devis, Yesica; Susmaneli, Herlina; Herniwanti, Herniwanti (Media Penelitian dan Pengembangan Kesehatan, 2023)
Workload is an important concern for the nursing profession which will have an impact on the performance of nursing staff in providing nursing services. This study aims to determine the results of measuring workload and performance of nursing staff in the Outpatient Installation of Dumai City Regional Hospital. The research method was quantitative with a cross-sectional study design. The research was conducted at the Dumai City Hospital Outpatient Installation from June-July 2023. The population of this study was 33 people, the sample used was 33 respondents taken using the total sampling technique. Workload measurement is carried out using the work sampling method through observation. Performance is obtained using secondary data. The data analysis used was univariate analysis and bivariate analysis with Pearson correlation, chi-square and linear regression on work sampling variables only. The research results showed that the calculation of heavy workload in orthopedic and neurosurgery clinics was 93.75%. With direct productive activities in wound care (19.23%) and indirect productive activities in completing the SPPK (Proof of Health Services) (13.01%). Nursing staff with a heavy workload was 27.28%, and a light workload was 72.72%. Nursing staff with good performance was 75.8% and very good 24.2%. There is no relationship between workload and the performance of nursing staff (p-value= 1.000, OR=0.750). Research Ethics Pass Letter Number: 145/KEPK/UHTP/VI/2023 dated June 19 2023. Evaluation and restructuring of work systems include reducing unproductive workloads, adjusting working hours, or allocating resources more efficiently and training and competency development of nursing staff.